The ones. Volume 1 - Bendis, Brian Michael (Dark Horse Books, a division of Dark Horse Comics LLC, 2023)
"Every single person in every mythology that was told they were THE ONE are brought together for the first time to defeat . . . THE ONE. The actual one. The real actual one. This amazing new vision is brought to life by wunderkind artist and co-creator Jacob Edgar (Batman, Army of Darkness). Watch as he brings explosive comics splendor to this big new world! Think Good Omens meets Ghostbusters meets The Adam Project meets The Goonies meets Everything Everywhere All at Once meets, um, anything else you've ever liked!"--